PENGARUH PEMBERIAN KAPUR DOLOMIT DAN KONSENTRASI PUPUK ORGANIK CAIR CAKRA BORNEO TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium cepa L.) - Ardaniah, Ardaniah (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2018)
The Onion red (Allium cepa L.) is a horticultural commodity belonging to spice vegetables. Spices vegetables are much needed, especially as a complement to cooking spices enhance taste and enjoyment of cuisine. In addition to cooking spices, red onions can also be used as a traditional medicine that is beneficial to health. The use of dolomite lime is able to increase the pH of the soil to be ideal and the plant becomes healthy, then liquid organic fertilizer can increase crop production.. This study aims to analyze the influence of interaction and dolomite lime single factor and concentration of liquid borneo liquid organic fertilizer on the growth and yield of shallot crop (Allium cepa L.). The research was carried out at Pama Daya Taka Business Development Institute, Sungai Terik Village, Batu Sopang Subdistrict, Paser Regency. This study used two factorial Randomized Block Design (RAK), the first factor was the Dolomite Lime treatment and the second factor was concentration Organic Fertilizer Liquid Cakra Borneo. Based on the results of the study showed that the treatment of lime dolomite and concentration of liquid organic fertilizers Cakra Borneo no significant effect on all parameters observed. While for interaction result between treatment of Lime of Dolomite and Dosage of Organic Fertilizer of Cakra Borneo Liquid have significant effect on leaf number parameter at age 3 MST. Keywords: Red onion, dosage, dolomite lime and POC Cakra Borneo